O pessoal é político: a violência sexual e de gênero como instrumento de manutenção do poder estatal no regime ditatorial argentino (1976-1983) - Carareto, Taís Souza (2020)
This research aims to examine the use of sexual and gender-based violence by the State during the military dictatorship in Argentina (1976-1983). In this sense, the main purpose is to analyze and explain in what ways the relationship between gender, body and violence is associated with the instrumental use of sexual and gender-based violence promoted by the State to maintain its power during the Argentine military regime. The hypothesis argues that, in this specific case, this model of violent action represents a political practice, based on gendered constructions, through which the State exercises its power through individual’s bodies. It is argued that the discourse of difference, by constructing the Other, the “internal enemy”, allowed bodies (especially the women’s ones) to be transformed into a space for political intervention and dispute, politicizing the body. Therefore, in order to prove this hypothesis, the specific bibliography will be reviewed and a quantitative analysis of official documents and reports will be made, using the theoretical-analytical framework offered by feminist theories of International Relations and gender studies.